STRATEGI PEMASARAN PRODUK PEMBIAYAAN WARUNG MIKRO PADA BANK SYARIAH MANDIRI KANTOR CABANG PROBOLINGGO - Maula Nasrifah; Aimatus Sholehah (Faculty of Islamic Economics and Business, 2020)
The purpose of this study to determine marketing strategy of Warung Micro finance products at Probolinggo Branch Office of Bank Syariah Mandiri as well as to determine the supporting and inhibiting factors for marketing the product. This study using a descriptive qualitative approach to the type of field research (flied research) through observations about a phenomenon. Data collection techniques are done by observation, interview, and documentation. The results of this study explain that the marketing strategy used by the Bank Syariah Mandiri Proboliggo Branch Office in an effort to achieve the target marketing of Warung Micro Fianance Products use a marketing mix strategy consist of Product, Price, Place and Promotion. While the promotion strategy used is a door to door strategy, advertising promotion strategy, pricing strategy, top-up strategy and product strategy. Supporting factors in the marketing of microfinance products are competitive product, low price and strategic location. While the inhibiting factors are the lack of public knowledge about the operational system of Islamic banks, competition between banks and the lack of human resources, especially human resources, microfinance sales so that marketing the product to the wider community takes a long time. Keyword: Strategy, Product, Finance